EFFECT OF PLANT GROWTH REGULATORS ON IN VITRO PLANT REGENERATION OF WHEAT (Triticum aestivum L.) F ROM EMBRYO EXPLANTS - Doriana (Bode) Xhulaj (Journal of Animal and Plant Sciences, 2019)
An efficient method was developed for multiple shoot regeneration of Albanian wheat (Triticum aestivum L.) cultivar “Dajti” from mature embryos without callus formation, for a short period of time. The effect of explants, isolated shoot embryonic meristem and shoot embryonic meristem with scutellum and various combinations of plant growth regulators in MS media on direct shoot regeneration of wheat was investigated. Among different combination of 2,4-D, IBA, NAA and BAP tested, embryo explants cultured in MS medium supplemented with 2 mg/L BAP, 0.6 mg/L 2,4-D resulted as the most efficient direct shoot regeneration and produces a maximum of 2.5 shoot per explants and 3.4 cm shoot length. Plantlets were successfully transferred to rooting medium. The greatest mean numbers of roots were obtained on MS media supplemented with 0.5 mg/L NAA, and the best mean value of root length (8.2 cm) at 0.5 mg/L IBA. In this paper by simple manipulating the concentrations of BAP, 2,4 D, IBA and NAA in the culture medium, is described a method for rapidly obtaining whole plants of wheat without the subculture, using embryo explants.
Keywords: embryo; direct shoot regeneration; growth regulators; rooting